Exceptional diversity of allorecognition receptors in a nonvertebrate chordate reveals principles of innate allelic discrimination - Henry Rodriguez-Valbuena; Jorge Salcedo; Olivier De Thier; Jean Francois Flot; Stefano Tiozzo; Anthony W. De Tomaso (Proceedings of the National Academy of Sciences, 2025)
Highly polymorphic allorecognition systems have been characterized in numerous invertebrate species, and exhibit discriminatory capabilities reminiscent of vertebrate adaptive immunity. As these systems utilize germline encoded receptors, the mechanisms underlying allelic discrimination are unknown. The invertebrate chordate, Botryllus schlosseri, undergoes a natural transplantation reaction controlled by a highly polymorphic, polygenic locus (called the fuhc) with over 1,000 allelic haplotypes found worldwide. Two individuals are compatible if they share one or both fuhc alleles, and we had found that polymorphic discrimination is due to the integration of signals from two allorecognition receptors encoded within the fuhc locus, called fester and uncle fester. Here we show that these two receptors are members of an extended family consisting of >35 genes, now called the Fester family ( FF ), and coexpressed with members of another diverse gene family, the fester coreceptors ( FcoR ). Both FF and FcoR are Immunoglobulin superfamily members and each FcoR encodes conserved tyrosine signal transduction motifs, including ITIMs or hemITAMs. FF and FcoR are expressed and encoded as cognate pairs in two polymorphic haplotypes: one within the fuhc locus, and another on a separate chromosome, and remarkably, copy number variation between haplotypes is of gene pairs. Furthermore, two FcoR genes can swap ITIMs and hemITAMs by alternative splicing, suggesting that dynamic tuning of activating and inhibitory signaling is required for allelic discrimination. These results indicate that conserved signal processing mechanisms are the foundation of both allelic discrimination in Botryllus , and recurring convergent evolution of allorecognition receptors observed from invertebrates to mammals.